2004
DOI: 10.1103/physrevd.70.034504
|View full text |Cite
|
Sign up to set email alerts
|

Scalar mesons in lattice QCD

Abstract: We explore whether ''f 0 (600) or '' exists as a pole in QCD, by a full lattice QCD simulation on the 8 3 ϫ16 lattice using the plaquette action and Wilson fermions. It is shown that there exists a pole, whose mass is as low as that of the , owing to the disconnected diagram of the meson propagator. A discussion is given on the physical content of the .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
115
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 28 publications
11
115
1
Order By: Relevance
“…With the lowest one corresponding to m π as low as 180 MeV, it is found that, when the quark mass is smaller than that of the strange, a 0 mass levels off, in contrast to those of a 1 and other hadrons that have been calculated on the lattice. This confirms the trend that has been observed in earlier works at higher quark masses in both the quenched and unquenched calculations [7,8,9,10]. The chiral extrapolated mass a 0 = 1.42 ± 0.13 GeV suggests that a 0 (1450) is a qq state.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…With the lowest one corresponding to m π as low as 180 MeV, it is found that, when the quark mass is smaller than that of the strange, a 0 mass levels off, in contrast to those of a 1 and other hadrons that have been calculated on the lattice. This confirms the trend that has been observed in earlier works at higher quark masses in both the quenched and unquenched calculations [7,8,9,10]. The chiral extrapolated mass a 0 = 1.42 ± 0.13 GeV suggests that a 0 (1450) is a qq state.…”
Section: Introductionsupporting
confidence: 79%
“…[20] seriously. We shall rely on the conclusion from the other calculations in both the quenched and unquenched calculations [6,7,8,9,10]. light scalar nonet is known to have a reversed ordering, namely, the scalar strange meson κ is lighter than the non-strange one such as f 0 (980), it has been proposed in [25] to consider the mixing of the qq heavy scalar nonet with the light nonet to make a 0 (1450) and K * 0 (1430) closer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early two-flavor dynamical simulations [3,4] reported values at or above 1.5 GeV, but later two-flavor dynamical calculations [6,7,8] obtained a ground state near 1 GeV. But is this the a 0 or πη ′ 2 ?…”
Section: Motivationmentioning
confidence: 99%
“…Indeed, recent years have seen considerable activity, concerning the calculation of the spectrum of the scalar mesons on the lattice (see, e.g., [25][26][27][28][29][30][31][32][33][34][35][36][37][38]). However, alone the calculations of the excited spectrum do not answer the question.…”
Section: Jhep01(2011)019mentioning
confidence: 99%